2019
DOI: 10.21203/rs.2.19697/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Creating mosquito-free outdoor spaces using transfluthrin-treated chairs and ribbons

Abstract: Background Residents of malaria-endemic communities spend several hours outdoors performing different activities, e.g. cooking, story-telling or eating, thereby exposing themselves to potentially-infectious mosquitoes. This compromises effectiveness of indoor interventions, notably long-lasting insecticide-treated nets (LLINs) and indoor residual spraying (IRS). This study characterized common peri-domestic spaces in rural south-eastern Tanzania, and assessed protective efficacies of hessian fabric mats and ri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…There have also been studies evaluating other transfluthrin-treated hessian emanators [ 42 ], chairs [ 45 ], artistic decorations [ 46 ] and sandals [ 47 ]. A combined analysis of these early studies shows that the transfluthrin-treated hessian products could: (i) retain protective efficacy for 6 months or more [ 42 ], (ii) be readily acceptable to local communities [ 39 , 46 ], (iii) be made locally without specialized skills needed, (iv) offer protection against indoor and outdoor mosquito bites [ 37 , 43 ], (v) have mosquitocidal effects [toxicity] in addition to repellency [ 48 ], and (vi) protect against multiple mosquito species including pyrethroid-resistant Anopheles [ 45 ]. The studies also showed that when used together with traps in push-pull systems, the protective benefit came primarily from the treated eave ribbons themselves [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…There have also been studies evaluating other transfluthrin-treated hessian emanators [ 42 ], chairs [ 45 ], artistic decorations [ 46 ] and sandals [ 47 ]. A combined analysis of these early studies shows that the transfluthrin-treated hessian products could: (i) retain protective efficacy for 6 months or more [ 42 ], (ii) be readily acceptable to local communities [ 39 , 46 ], (iii) be made locally without specialized skills needed, (iv) offer protection against indoor and outdoor mosquito bites [ 37 , 43 ], (v) have mosquitocidal effects [toxicity] in addition to repellency [ 48 ], and (vi) protect against multiple mosquito species including pyrethroid-resistant Anopheles [ 45 ]. The studies also showed that when used together with traps in push-pull systems, the protective benefit came primarily from the treated eave ribbons themselves [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…funestus mosquitoes which are known to be resistant to pyrethroids. Hence eave ribbons have potential in managing insecticide resistance Masalu et al [ 45 ] 10 Predicting the impact of outdoor vector control interventions on malaria transmission intensity from semi-field studies Statistical modelling of semi field eave ribbons data from Tanzania and Kenya Laboratory-reared Anopheles arabiensis 41–96% Transfluthrin treated eave ribbons provide both personal and community protection. Denz et al [ 49 ] 11 Transfluthrin Eave-Positioned Targeted Insecticide (EPTI) Reduces Human Landing Rate of Pyrethroid Resistant and Susceptible Malaria Vectors in a Semi Field Simulated Peri-domestic Space Eave ribbons were treated following the procedures described by Mmbando et al [ 37 ] Laboratory-reared Anopheles arabiensis 80% 68% Transfluthrin treated eave ribbons have potential tackle the challenges of insecticide resistance in malaria vectors Tambwe et al [ 56 ] 12 Evaluating putative repellent ‘push’ and attractive ‘pull’ components for manipulating the odour orientation of host-seeking malaria vectors in the peri-domestic space Hessian strip [21 m × 0.05 cm] impregnated with 10 ml technical grade transfluthrin prepared in soapy water; the strips suspended overnight indoors to dry Tests were done in large semi-field cage Laboratory-reared Anopheles arabiensis Not assessed 94% Transfluthrin treated hessian fabric strips around eave gaps provide significant protection from mosquito bites in the peri-domestic spaces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…arabiensis poses a challenge to malaria vector control. Larval source management with microbial larvicides combined with LLINs has been shown to be protective against malaria infections in rural Kenya [69], and there are several measures including treating cattle with insecticide [60], use of odor-baited traps dispensing spatial repellents [70], and trans uthrin-treated chairs and ribbons [71], which could be deployed as control interventions in the future. In Uganda, there is still an information gap regarding the zoophilic behavior of An.…”
Section: Discussionmentioning
confidence: 99%